Desensitization: Overcoming the Immunologic Barriers to Transplantation. (3rd January 2017) - Sethi, Supreet; Choi, Jua; Toyoda, Mieko; Vo, Ashley; Peng, Alice; Jordan, Stanley C.
Abstract : HLA (Human Leucocyte Antigen) sensitization is a significant barrier to successful kidney transplantation. It often translates into difficult crossmatch before transplant and increased risk of acute and chronic antibody mediated rejection after transplant. Over the last decade, several immunomodulatory therapies have emerged allowing for increased access to kidney transplantation for the immunologically disadvantaged group of HLA sensitized end stage kidney disease patients. These include IgG inactivating agents, anti-cytokine antibodies, costimulatory molecule blockers, complement inhibitors, and agents targeting plasma cells. In this review, we discuss currently available agents for desensitization and provide a brief analysis of data on novel biologics, which will likely improve desensitization outcomes, and have potential implications in treatment of antibody mediated rejection.